2016
DOI: 10.1097/md.0000000000005541
|View full text |Cite
|
Sign up to set email alerts
|

Role of immune cells in pancreatic cancer from bench to clinical application

Abstract: Background:Pancreatic cancer (PC) remains difficult to treat, despite the recent advances in various anticancer therapies. Immuno-inflammatory response is considered to be a major risk factor for the development of PC in addition to a combination of genetic background and environmental factors. Although patients with PC exhibit evidence of systemic immune dysfunction, the PC microenvironment is replete with immune cells.Methods:We searched PubMed for all relevant English language articles published up to March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 166 publications
(216 reference statements)
3
109
1
Order By: Relevance
“…Tumour-educated TAMs facilitate progression of pancreatic cancer and promote angiogenesis, remodelling of stroma, epithelial-mesenchymal transition and extravasation of tumour cells [28, 29]. Previous studies have demonstrated that TAMs are associated with poor prognosis in pancreatic cancer [7, 8], which is in line with the findings of the present study encompassing the full spectrum of periampullary adenocarcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…Tumour-educated TAMs facilitate progression of pancreatic cancer and promote angiogenesis, remodelling of stroma, epithelial-mesenchymal transition and extravasation of tumour cells [28, 29]. Previous studies have demonstrated that TAMs are associated with poor prognosis in pancreatic cancer [7, 8], which is in line with the findings of the present study encompassing the full spectrum of periampullary adenocarcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, PDA cells compose only a minority of tumor bulk, with the majority (up to 80%) being accounted for by fibrotic tissue and inflammatory cells. Early in the course of carcinogenesis, acute and chronic inflammation activate pancreatic stellate cells (PaSC), which in turn, trigger the accumulation of a dense extracellular matrix, thereby disrupting the architecture of normal pancreatic tissue and inducing a hypovascular and hypoxic microenvironment . Several systemic agents targeting the PDA desmoplastic stroma have been devised and tested, alone or with cytotoxic chemotherapy.…”
Section: Pancreatic Cancer Microenvironmentmentioning
confidence: 99%
“…In addition to posing a physical barrier to the infiltration of cytotoxic immune cells, the PDA microenvironment is characterized by cytokines, chemokines, and suppressor cells that inhibit the activation and function of immune effectors . While infiltrating effector T cells are abundant in tumors that tend to respond to checkpoint inhibitors, such as melanoma or microsatellite unstable colorectal cancer, PDA tumors are infiltrated by fibroblasts, myeloid‐derived suppressor cells, and T regulatory cells but relatively few cytotoxic T cells .…”
Section: Pancreatic Cancer Microenvironmentmentioning
confidence: 99%
“…Macrophages arrive to sites of inflammation after neutrophils and persist longer [40]; indeed, they are one of the main cell types involved in chronic inflammation [11, 41]. They infiltrate tumors in response to DAMPs and other danger signals are released secondary to tissue stress and hypoxia (which might be a consequence of chemo-/radio-therapy).…”
Section: Tissue Stress Inflammation and Carcinogenesismentioning
confidence: 99%
“…They infiltrate tumors in response to DAMPs and other danger signals are released secondary to tissue stress and hypoxia (which might be a consequence of chemo-/radio-therapy). They also mount responses to attempt to counteract danger signals and tissue stress; these include angiogenesis , remodeling of the ECM, and clearance of cellular debris [41]. Importantly, in mouse models of pancreatitis, they have been found to directly promote ADM via release of the pro-inflammatory cytokines RANTES and TNF, which activate NF-κB in acinar cells and upregulate several ADM-related proteins such as MMP9 [42].…”
Section: Tissue Stress Inflammation and Carcinogenesismentioning
confidence: 99%